Design of Information System for Reporting Service Indicators at Imelda Hospital in 2023 - Karo-Karo, Siddik; Simamora, Bitcar Praja (Jurnal Komputer Indonesia (Ju-Komi), 2023)
The service indicator reporting information system at Imelda Hospital is designed for data processing and information presentation, especially about hospital service indicator reporting data that is easily accessible to officers anywhere and anytime, and can help the data processing process that will produce information so that the system work process can be well integrated and does not require a long time to search for data, data processing, and storing data. This study aims to design and create a Service Indicator Reporting Information System in hospitals and make it easier for officers to be faster and more precise in their services. This type of research uses a phenomenological approach method where researchers try to understand deeply the phenomenon under study. The results of this research show that the number of beds in the SIMRS application at IPI General Hospital. Where the number of beds in the SIMRS application is 322 beds while the actual number of beds or registered in the operational permit of IPI RSU is 276 beds. So that it greatly affects the report of hospital indicators at IPI General Hospital. Overall, the system that the author proposes has been proven to be more precise, fast and accurate than the results of reports from SIMRSU IPI and or from the results of manual calculations carried out by officers when reporting in the previous period. The hospital service indicator report produced by the system proposed by the author is better than the report produced by SIMRSU IPI. However, the overall report on hospital service indicators at IPI Hospital is still below the standards of the Ministry of Health.